TTF2 Gene Mutation in Neonates with Congenital Hypothyroidism Caused by Thyroid Dysgenesis - Frouzande Mahjoubi (مجله دانشکده پزشکی اصفهان, 2012)
Background: Thyroid transcription factor 2 (TTF2) or forkhead box E1 (FOXE1) is a polyalanine domain protein with an important role in the morphogenesis and development of thyroid gland. Mutations of TTF2 gene have been identified in neonates with congenital hypothyroidism caused by thyroid dysgenesis. In this study, the mutations of TTF2 gene were studied among these patients. Methods: In this study, the entire TTF2 gene of 50 neonates with congenital hypothyroidism due to thyroid dysgenesis who referred to Isfahan Endocrine and Metabolism Research Center (Isfahan, Iran) was studied by direct DNA sequencing. The mutations were assessed after amplification of TTF2 gene by polymerase chain reaction (PCR) method. Mutations of each exon of TTF2 gene were evaluated by the adjacent primers of the whole encoding region. Findings: We did not find any mutation in TTF2 gene. There was a serotonin polymorphism among 74% of studied patients. The length of TTF2 polyalanine tract was 14 amino acids in most patients. Conclusion: The findings of   this study indicated the possible correlation between TTF2 polyalanine tract length polymorphism and genetic susceptibility to thyroid dysgenesis among patients with congenital hypothyroidism. Keywords: Congenital hypothyroidism, Thyroid transcription factor 2, Thyroid dysgenesis